2019
DOI: 10.1002/cam4.2399
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, immunogenicity and safety of the AS04‐HPV‐16/18 vaccine in Chinese women aged 18‐25 years: End‐of‐study results from a phase II/III, randomised, controlled trial

Abstract: BackgroundCervical cancer is a major public health concern in China. We report the end‐of‐study results of a phase II/III trial to assess the efficacy, immunogenicity, and safety of the AS04‐human papillomavirus (HPV)‐16/18 vaccine in Chinese women aged 18‐25 years followed for up to 72 months after first vaccination. Results of approximately 57 months following first vaccination have been previously reported.MethodsHealthy 18‐25‐year‐old women (N = 6051) were randomized (1:1) to receive three doses of AS04‐HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 41 publications
6
29
2
1
Order By: Relevance
“…The China Food and Drug Administration approved the 2vHPV vaccine in July 2016, which was a groundbreaking decision by the Chinese authorities. Long-term follow-up of clinical studies of the efficacy of 2vHPV vaccine in Chinese women has shown that the effect of the vaccine is consistent with the results of a global study (84). The vaccine is highly immunogenic to Chinese women and does not cause serious adverse reactions.…”
Section: Progress In Vaccination Of Hpv Vaccines In Chinasupporting
confidence: 59%
“…The China Food and Drug Administration approved the 2vHPV vaccine in July 2016, which was a groundbreaking decision by the Chinese authorities. Long-term follow-up of clinical studies of the efficacy of 2vHPV vaccine in Chinese women has shown that the effect of the vaccine is consistent with the results of a global study (84). The vaccine is highly immunogenic to Chinese women and does not cause serious adverse reactions.…”
Section: Progress In Vaccination Of Hpv Vaccines In Chinasupporting
confidence: 59%
“…1 With the development of the prophylactic HPV vaccination and CC screening, the 5-year overall survival (OS) rate of CC has been prolonged. 2 However, in many developing countries, the 3-to 5-year OS rate of CC is less than 50%; especially in patients with advanced disease, the recurrence rate of CC is as high as 70%. 3,4 The cure rate for recurrent CC is very low, and the 5-year survival rate for relapsed patients is less than 5%.…”
Section: Introductionmentioning
confidence: 99%
“…26,35 Although not unequivocal, the immune response elicited after natural infection with HPV can reduce the risk of reinfection with the same HPV type. 36,37 [31][32][33] The exact mechanism of protection conferred by HPV vaccination is still to be fully elucidated. Strong and persistent neutralizing antibody levels together with cellular immune response triggered by the vaccine are thought to be involved in its ability to protect the host from HPV infections, even though they may not be the only mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…These seropositivity rates were higher compared to the persistence rates reported by Zhu and colleagues 6 years after first vaccine dose in women from the pivotal efficacy study. 32 (Table 2). These values were, respectively, 2-and 1.5-fold higher than compared to antibody GMCs measured 6 years after vaccination of women aged 18-25 years in the pivotal efficacy study 32 (presented in Table 2 for comparison).…”
Section: Immunogenicitymentioning
confidence: 99%
See 1 more Smart Citation